General relativistic modeling of pulsars with radiative effects - Mardan, S. A.; Khalid, A.; Zahra, A.; Riaz, Muhammad Bilal; Ditta, Allah; Zulqarnain, Rana Muhammad (World Scientific Publ Co Pte Ltd, 2026)
In this paper, we proposed a general model for static spherically symmetric compact stars by incorporating anisotropic pressure and a modified Van der Waal (VdW) Equation of State (EoS). The inclusion of radiation density in the energy-momentum tensor, which provides a more realistic description of high-energy stellar interiors. The calculated solutions satisfy all necessary physical conditions like energy conditions, causality conditions and interior spacetime smoothly match with Vaidya exterior spacetime. The resulting key physical quantities such as density, pressure, mass, and redshift are stable and well-behaved throughout the stellar interior. The theoretical data correspond closely with observational constraints obtained from massive pulsars like PSR J0030+0451, PSR J0740+6620, and PSR J0348+0432. These findings highlight the significant role of radiation density in shaping the structure and stability of pulsars and support the applicability of the proposed model.
Keywords: Van der Waal equation; Radiation density; anisotropy; Vaidya spacetime; Pulsars